Measurement of the difference of time-integrated CP asymmetries in D0→K-K+ and D0→π-π+ decays - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Esen, Sevda; Gerick, David; Gersabeck, Evelina; Grillo, Lucia; Han, Xiaoxue; et al. (Physical review letters, 2016)
A search for CP violation in D0→K−K+ and D0→π−π+ decays is performed using pp collision data, corresponding to an integrated luminosity of 3 fb−1, collected using the LHCb detector at center-of-mass energies of 7 and 8 TeV. The flavor of the charm meson is inferred from the charge of the pion in D*+→D0π+ and D*−→¯¯¯D0π− decays. The difference between the CP asymmetries in D0→K−K+ and D0→π−π+ decays, ΔACP≡ACP(K−K+)−ACP(π−π+), is measured to be [−0.10±0.08(stat)±0.03(syst)]%. This is the most precise measurement of a time-integrated CP asymmetry in the charm sector from a single experiment.